1993
DOI: 10.1073/pnas.90.23.11049
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of human T-cell clones by Herpesvirus saimiri: intact antigen recognition by autonomously growing myelin basic protein-specific T cells.

Abstract: Herpesvirus saimiri has recently been shown to immortalize human T cels. It was unknown, however, whether Herpesvirus saimiri transformation affects T-cell receptor (TCR) expression and signal transduction. In the present study, we have transformed CD4+ human T-cell clones speciffc for human myelin basic protein. The transformed T cells were grown in interleukin 2 and divided in the absence of antigen and antigen-presenting ceUls. They retained the membrane phenotype of activated T ceUs and secreted the cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…Among many preserved relevant functions of normal T cells, the MHC-restricted antigen specificity of parental T cell clones is the most important feature. [35][36][37][38][39] A broad variety of T cell subtypes can be transformed, either CD4 + or CD8 + cells, and either ␣␤-or ␥␦-T cells. 32,37,[44][45][46][47] When polyclonal bulk cultures had been infected with the virus, a broad spectrum of V␤ chains was represented in the resulting transformed cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many preserved relevant functions of normal T cells, the MHC-restricted antigen specificity of parental T cell clones is the most important feature. [35][36][37][38][39] A broad variety of T cell subtypes can be transformed, either CD4 + or CD8 + cells, and either ␣␤-or ␥␦-T cells. 32,37,[44][45][46][47] When polyclonal bulk cultures had been infected with the virus, a broad spectrum of V␤ chains was represented in the resulting transformed cultures.…”
Section: Discussionmentioning
confidence: 99%
“…32 In contrast to leukemic cell lines or to HTLV-1 immortalized T cells, the herpesvirus-transformed human T lymphocytes retain a high degree of functionality including the MHC-restricted antigen-specific reactivity of parental non-infected T cell clones. [35][36][37][38][39] There is only little virus gene expression and no virion production in these T cells. 33,40 The C488-transformed human T cells appear to be non-tumorigenic.…”
mentioning
confidence: 99%
“…The Herpesvirus saimiri-transformed SS8T human T cell clone (22) restricted by DRB5*0101 and MBP(84-102) was cultured in RPMI 1640 medium supplemented with 2 mM L-glutamine, 100 units/ml penicillin, 100 l g/ml streptomycin, 10% fetal bovine serum (Hyclone), and 50 units/ml human recombinant interleukin-2 (from ABI) at 37 ± C. Every alternate day the cells were transferred to fresh medium. Various LMW and HMW complex preparations were coated onto a microtiter tissue culture plate, and the cells were inoculated at a density of 20 000/well in 200 l l of medium without interleukin-2.…”
Section: Reloading Of Lmw and Hmw Aggregate Class II Complexes And Qumentioning
confidence: 99%
“…3,4 More recently, it has been reported that certain strains of Herpesvirus saimiri (HVS) immortalize human T lymphocytes (HVS-T), thus yielding long-term cell lines with stable surface markers and functional phenotypes. 5,6 This strategy has provided a suitable, convenient experimental approach to examine T-cell function. HVS is non-pathogenic in its natural host, the squirrel monkey, but provokes extremely aggressive lymphomas and lymphocytic leukemias in other primates, 7 where it enters the cell and remains as nonintegrated viral episomes.…”
Section: Introductionmentioning
confidence: 99%
“…HVS is non-pathogenic in its natural host, the squirrel monkey, but provokes extremely aggressive lymphomas and lymphocytic leukemias in other primates, 7 where it enters the cell and remains as nonintegrated viral episomes. 5,6 Although HVS encodes two antiapoptotic proteins, 8,9 all evidence suggests that it is not interference with apoptotic programs that promotes HVS immortalization of T cells but rather interactions between viral proteins and normal T-cell signaling pathways. 10 HVS-T cells are potentially important in the study of both primary and acquired immunodeficiencies.…”
Section: Introductionmentioning
confidence: 99%